GENERAL CONSIDERATIONS ON EUROPEAN SPECIAL CUSTOMS PROCEDURES - POPEANGĂ VASILE NICOLAE (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2023)
To achieve the projected objectives of the European customs policy, customs regimes play a decisive role. Within them, the special ones are extremely important, because they provide economic operators with a series of facilities, which allow them to increase their competitiveness in the global commercial competition. In our analysis, we carry out a review of the normative and operational requirements of each special customs regime, as well as a presentation of its advantages, noting their overall positive contribution to the activity of European entrepreneurs.